Proposed Project Management System for PT. GTU: A Case Study of Piping System Construction Project - Abizar, Muhammad Rival; Yudoko, Gatot (Universitas KH. Abdul Chalim Mojokerto, 2026)
Engineering, procurement and construction (EPC) projects place a single contractor in charge of design, materials and construction under tight time and cost targets. In Indonesia many projects also rely on subcontractor labor and owner supplied materials, which increases coordination risk. PT GTU experienced a failure on a piping project for a paper mill in Riau, known as BM4. This thesis examines why the project moved away from its plan and what kind of project management system could have reduced the likelihood of failure. BM4 is analysed as a single case. The study assumes that complex projects usually fail because of an accumulation of management choices rather than one event. It aims to identify the key factors behind the failure using the six project constraints as a frame, to explain how they affected schedule, site readiness, subcontractors and cash flow, and to develop a project management system tailored to GTU. A qualitative design is used. Data comes from semi structured interviews with seven internal stakeholders and from supporting project documents. The material is coded by project constraints, analyzed using Current Reality Trees to link visible symptoms to root causes, and compared with selected PMBOK Guide Sixth Edition processes as a benchmark for expected practice. The results indicate three main root causes: lack of project leadership and discipline, absence of formal change control and unrealistic schedule and resource baselines. Together they explain the difficulties in BM4, including unstable subcontractor manpower, coordination problems and repeated quality issues. The thesis concludes by proposing a practical project management system for GTU that clarifies governance routines, introduces an integrated change control procedure and strengthens rules for setting and updating baselines to support future EPC projects.